Iceland : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
Iceland's 2005 Article IV Consultation reports that new projects have rekindled rapid growth and the economy is exhibiting signs of overheating, with imbalances evident in inflation, the current account, and external debt. GDP grew at an average rate of 3.8 percent between 1995 and 2004, second only to Ireland among industrial countries. Major investment projects have contributed both to the high growth rate and to overall macroeconomic volatility because of their size relative to that of the economy.